KONSTRUKSI SOSIAL BUDAYA “GANJUR(AN)”DI DESA CANDITUNGGAL, KABUPATEN LAMONGAN - Inayati, Nurul; Nugroho, Wahyu Budi; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT Cultural social construction “ganjura(an)” for weddings at Canditunggal, Lamongan can be analized through cultural social study. This research aims to discuss and set out the social construct of ganjuran that occurs among Lamongan people especially in Canditunggal. This research uses descritive-explanatory qualitative research method with the social constructive theory by Peter L. Berger and Thomas Luckman as the society is seen as double facts, objective and subjective. There are three dialectical moments which are externalization, internalization, and objectification. Based on the research it is found that social construct toward ganjuran culture in Canditunggal society, in Lamongan is about the ganjuran culture itself is going to be uphold using the intial method though there are unsignificant changes. Those are a transformation in a gawan that changing the materials of foods into valuable things such as money. Keywords: Social construct, Culture, and Ganjuran